REHABILITASI TANAH SAWAH TERCEMAR LOGAM BERAT Pb DAN Cd MELALUI FITOREMEDIASI - Sandra Sukmaning Adji (LPPM Universitas Terbuka, 2005)
It is indicated that rice field soil and plants on Rancaekek Bandung is containing heavy metal elements. This research aims to find out rehabilitation method for rice field soil by phytoremediation. Experiment was conducted in greenhouse. Vegetation used for this research were eceng gondok, mendong, akar wangi and haramay. The vegetation treatment was conducted under greenhouse experiments using Complete Randomized Design (CRD). Result showed that the use of vegetation had reduced the volume of Pb and Cd in the soil. Heavy metals are also contained within the roots and the leaves of the indicator plants. Mendong contained the highest concentration of Pb accumulated in its root, while akar wangi was indicated as contained Cd in its roots. Eceng gondok was indicated as containing the highest consentration of Pb and Cd accumulated in its leaves